Krisis Regenerasi Petani dan Implikasinya terhadap Ketahanan Pangan Nasional di Indonesia - Anja Kelauri, Suastiana; Lokot Muda Harahap; Enzelika Rosari Putri; Febri Milano Sagala (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2026)
The agricultural sector plays a crucial role in Indonesia’s economy as it functions as a provider of food supply, a source of employment, and a key pillar of national food security. However, the sector is currently facing a significant challenge in the form of a farmer regeneration crisis. This issue is reflected in the declining interest of younger generations in pursuing careers in agriculture and the increasing average age of farmers in Indonesia. Such conditions may threaten the sustainability of food production in the future. This study aims to analyze the challenges related to farmer regeneration in Indonesia and examine their implications for national food security. The research employs a descriptive qualitative approach using literature review and document analysis methods. Data were collected from various scientific sources, including academic journals, books, research reports, and official publications relevant to the research topic. The findings indicate that the low interest of young people in the agricultural sector is influenced by several factors, such as the perception of relatively low income in agriculture, limited access to land and capital, and the lack of technological innovation in agricultural activities. The farmer regeneration crisis may lead to a decline in agricultural productivity and increase dependence on food imports. Therefore, strategic efforts are needed, including agricultural modernization, the development of millennial farmer programs, and supportive government policies to encourage youth participation in agriculture and strengthen national food security.